"In Today's Society, It's a Necessity": Latino/a Postsecondary Plans in the College-for-all Era. (April 2017) - Ovink, Sarah M.
Latino/a enrollments at U.S. colleges are rapidly increasing. However, Latinos/as remain underrepresented at four-year universities, and college completion rates and household earnings lag other groups'. Yet, little theoretical attention has been paid to the processes that drive these trends, or to what happens when students not traditionally expected to attend college begin to enroll in large numbers. Longitudinal interviews with 50 Latino/a college aspirants in the San Francisco East Bay Area reveal near-universal college enrollment among these mostly low-income youth, despite significant barriers. East Bay Latino/a youth draw on a set of interrelated logics (economic, regional, family/group, college-for-all) supporting their enrollment, because they conclude that higher education is necessary for socioeconomic mobility. In contrast to the predictions of status attainment and rational choice models, these rationally optimistic college aspirants largely ignore known risks, instead focusing on anticipated gains. Given a postrecession environment featuring increasing costs and uncertain employment, this approach led many to enroll in low-cost, less supportive two-year institutions, resulting in long and winding pathways for some. Results suggest that without structural supports, access to college fails to meaningfully redress stratification processes in higher education and the postrecession economy that significantly shape possibilities for mobility.